2017
DOI: 10.1016/j.jsps.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different proportions of astragaloside and curcumin on DM model of mice

Abstract: This paper aims to study the effects of different proportion of astragaloside and curcumin on STZ induced Diabetes Mellitus (DM) model of mice, and to select a better proportion of active components. Its ultimate purpose is to lay a basis for the follow-up research on astragaloside-curcumin capsule. Increase-decrease baseline geometric proportion design method and comprehensive performance evaluation utilised to study the effect of different proportion of astragaloside and curcumin on DM mice models, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…AS-IV significantly increases the content of hepatic glycogen and insulin, decreases the content of blood glucose glycated serum protein, and significantly improves pancreatic pathological changes in streptozotocin-induced diabetic mice. 99 By downregulating the expression of IL-6 and TNF-α and inhibiting the NLRP3 inflammasome in the pancreas of gestational diabetic mice, AS-IV can reduce glucose and insulin levels in gestational diabetic mice. 100 Moreover, it can inhibit the expression of integrin-linked kinases in diabetic rats and restore the expression of integrin α3β1 to reduce diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…AS-IV significantly increases the content of hepatic glycogen and insulin, decreases the content of blood glucose glycated serum protein, and significantly improves pancreatic pathological changes in streptozotocin-induced diabetic mice. 99 By downregulating the expression of IL-6 and TNF-α and inhibiting the NLRP3 inflammasome in the pancreas of gestational diabetic mice, AS-IV can reduce glucose and insulin levels in gestational diabetic mice. 100 Moreover, it can inhibit the expression of integrin-linked kinases in diabetic rats and restore the expression of integrin α3β1 to reduce diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…When considered in the context of the results of previous studies, our findings suggest that astragaloside IV could ameliorate hyperglycemia through multiple pathways (e.g., IKK/IjBa and IRS/AKT pathways) and alleviate hyperlipidemia through mediation of blood lipid metabolism-related enzymes (e.g., Akt-dependent phosphodiesterase 3B). [17][18][19]21 Oxidative stress is a major pathological process associated with an increased risk of cardiovascular disease in DM patients, and astragaloside IV comprises a promising regulatory treatment that may reduce damage caused by oxidative stress in various conditions. 7,22 A previous in vitro experiment revealed that astragaloside IV can protect apolipoprotein E-deficient mice from cardiac remodeling through the regulation of multiple pathways and pathological processes, including the reduction of oxidative stress through reversal of oxidantantioxidant effects in heart tissue.…”
Section: Discussionmentioning
confidence: 99%
“…When considered in the context of the results of previous studies, our findings suggest that astragaloside IV could ameliorate hyperglycemia through multiple pathways (e.g., IKK/IκBα and IRS/AKT pathways) and alleviate hyperlipidemia through mediation of blood lipid metabolism-related enzymes (e.g., Akt-dependent phosphodiesterase 3B). 17 19 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…The baseline geometric design method [ 17 ] was used and the baseline combination of Astragalus–Angelica was set at 5:1, and the Astragalus and Angelica dosage was increased or decreased by 16.6% on both sides in order to design different combinations of Astragalus–Angelica, in addition with the positive drug atorvastatin group (10 mg/kg). Sprague–Dawley rats were randomly divided into normal group (the left common carotid artery was exposed and ligated, but the balloon was not used), model group (the model was given normal saline with the same volume of the drug group by intragastric administration), Astragalus and Angelica with single use or different ratios groups, and atorvastatin group.…”
Section: Methodsmentioning
confidence: 99%